Comportement vis-à-vis des attaques sulfatiques et de la carbonatation d’un béton autoplaçant à base de sédiment de dragage - BELGUESMIA KHALIL (My University, 2012)
Because of the specificities of self-compacting concrete (SCC), especially regarding their high volume paste content and the presence of large amounts of mineral admixtures and substitutes, the behaviour in fresh and hardened state and the durability of these concretes are strongly influenced by these two parameters. Sediments treated with pozzolanic properties can be used as additions or substitutes to the cement, this possibility makes of concrete technology a privileged way of enhancement. This study aims to contribute to the enhancement of the treated mud of Chorfa II dam (Algeria) as a mineral substitute for CPA CEMI 42.5 cement in the composition of an economic and preferment self-compacting concrete. the aim is to compare the influence of this calcined mud to the natural pozzolan of Beni Saf (Algeria) on the physical, mechanical behaviour and durability of these concretes in the short-term (28 days) and medium-term (90 days). Two formulations were studied, thus covering one strength classes, as well as two types of concrete: SCC with natural pozzolan (SCC-PZ), and SCC with calcined mud (SCC-V). The SCC containing calcined mud represents not only an economic SCC but also performances quite comparables to those obtained on SCC containing natural pozzolan. The results obtained of the compressive strength are very close with a slight superiority for the BAP-V in the short term. The results of the different following tests: carbonation and sulphates attacks (Na2SO4 and MgSO4) show that the calcined mud has an influence roughly better than the natural pozzolan on the physico-mechanical behaviour and durability of the SCC.
Keywords: s: Dam of Chorfa – mud – pouzzolan – SCC containing mud - SCC containing pouzzolan – mechanical strength –Durability.